Acoustic emission behavior of polyvinyl alcohol (PVA) fiber reinforced calcium sulphoaluminate cement mortar under flexural load. (August 2021) - Li, Jingjun; Yan, Jun; Xue, Gang; Niu, Jiangang
Abstract: The purpose of this study was to study the failure mechanism, fiber bridging and slip mechanism of PVA fiber reinforced calcium sulphoaluminate cement mortar (CSAM) under bending load. Firstly, the flexural toughness performance of PVA fiber reinforced CSAM was studied. Then, the change of acoustic emission (AE) behaviors was studied, including the change of AE parameters (counts and energy), the cracking mode reflected by the average frequency (AF) and RA values, the peak frequency and Ib value. The results showed that PVA fiber could significantly improve the flexural properties of CSAM. In contrast to PVA0, the AE count and energy of fiber reinforced CSAM remained at a high level after the peak load. The excellent bonding property between fibers and MPC paste didn't always lead to the strong local maximum of RA and the strong local minimum of AF at the time of main fracture. Compared with PVA fiber reinforced CSAM, the failure of specimen PVA0 was only controlled by tensile cracks. The peak frequency bands of 20–50 kHz, 90–110 kHz and 290–320 kHz, respectively corresponded to the friction and pull-out of the fiber, the matrix cracking of CSAM and the propagation and development of macro-cracks. Highlights: PVA fiber reinforced CSAM under flexural load is studied. Variation of AE behaviors is studied. Failure mechanism and fiber bridging of PVA fiber reinforced CSAM are revealed.